Pemanfaatan Scan Barcode Dalam Penyuluhan Kesehatan Hipertensi Untuk Lansia: Studi Kasus di Posyandu Mekarsari: Pemanfaatan Scan Barcode Dalam Penyuluhan Kesehatan Hipertensi Untuk Lansia: Studi Kasus di Posyandu Mekarsari - Purnaningrum, Ambar; Annis, Chanifa Fitria; Pratiwi, Ririn Indah; Alfiyanti, Dera (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2025)
Hypertension is a major health problem among the elderly, with high prevalence and often undetected due to limited knowledge and access to information. Health education innovations using digital technology, such as barcode (QR code) scanning, are needed to improve the effectiveness of counseling. This study aimed to evaluate the impact of hypertension education using barcode scanning on elderly knowledge at Posyandu Mekarsari. The method combined lectures, group discussions, leaflets, and QR code media integrated with digital educational materials, accompanied by blood pressure measurement and supportive activities such as light exercise. Evaluation was conducted using pre-test and post-test among 10 elderly participants. The results showed a significant increase in knowledge levels, from the majority in the moderate category (80%) before the intervention to the majority in the high category (90%) after the intervention. These findings demonstrate that the use of barcode scanning is effective in improving elderly knowledge and awareness regarding the prevention and management of hypertension, while also strengthening the role of posyandu as a health education center. It is recommended that this program be further developed with continuous training to ensure optimal use of technology by the elderly.